PEMBELAJARAN KIMIA ANALITIK BERBASIS MASALAH DENGAN MENGGUNAKAN METODE INKUIRI TERBIMBING DAN PROYEK DITINJAU DARI KREATIVITAS DAN INTERAKSI SOSIAL MAHASISWA - Susilowati, Indah Tri; Ashadi, Ashadi; Raharjo, Sentot Budi (Jurnal Inkuiri, 2013)
method which was creativity, social interaction and itâs interaction toward studentsâcognitive, affective andpsychomotor learning achievement. The method used in the research was experimental method and wasconducted from September 2011 to February 2012. The population was the students of D-III Nasional Academyof Health Analyst Surakarta level I who had taken the analitycal chemistry I lecture. The sample was taken byusing cluster random sampling, consisted of two class regular 1B.1 and regular 1B.2. The learning methodapplied on regular 1B.1 was guided inquiry and on regular 1B.2 was project. The data was collected throughstudentsâcognitive learning achievement test, and supported by questioner for measuring affective achievementsand observation sheet for assessing psychomotor. The hypothesis were tested using ANOVA three factorialdesigns with non-equal cell. From the data analysis, it could be concluded that: 1) there was no significantdifference from the results of Guided Inquiry and Project Method towards studentsâ learning achievement, 2)there was no significant difference from the results of high creativity and low creativity studentsâ learningachievement, 3) there was no significant difference from the results of high social interaction and low socialinteraction studentsâ learning achievement, 4) there was no interaction between learning method and creativitytoward studentsâ learning achievement, 5) there was no interaction between learning method and socialinteraction toward studentsâ learning achievement, 6) there was no interaction between creativity and socialinteraction toward studentsâ learning achievement, 7) there was no interaction among learning method,creativity, and social interaction toward studentsâ learning achievement.Keywords: Problem-based learning, Guided Inquiry Method, Project Method, Creativity, Social Interaction.